Material Christianity in the Early Medieval Household - Smith, Julia M. H. (Studies in church history, 2014)
Tu autem cum oraveris, intra in cubiculum tuum, et clauso ostio, ora Patrem tuum in abscondito: et Pater tuus, qui videt in abscondito, reddet tibi. (‘But when you pray, go into your room and shut the door. Pray to your Father in private, and your Father, who sees into concealed places, will reward you’: Matt. 6: 6)Manuscript D.V.3 in the Biblioteca Nazionale of Turin is a fat, late eighth-century volume of martyr narratives. Produced at Soissons, probably in the nunnery of Notre-Dame, it may be no coincidence that eighteen of its forty texts concern female martyrs. A further four address familial groups in which wives or mothers play prominent roles. The earliest Latin version of the passion of St Adrian (BHL 3744) is among them: one of many late, ‘novel-esque’ accounts of martyrdom, it is constructed out of clichéd formulae and predictable tropes for post-persecution audiences, like others of its genre. Lacking any historical verisimilitude about the age of persecutions, the passion of Adrian is characteristic of this group of hagiographies in offering valuable insights into domestic Christianity in the age in which it was composed: it brings into sharp focus links between women and material Christianity within the late antique household, the theme this essay pursues into the Carolingian period.